2003
DOI: 10.1152/ajpgi.00396.2002
|View full text |Cite
|
Sign up to set email alerts
|

Anion-dependent Mg2+influx and a role for a vacuolar H+-ATPase in sheep ruminal epithelial cells

Abstract: The K+-insensitive component of Mg2+ influx in primary culture of ruminal epithelial cells (REC) was examined by means of fluorescence techniques. The effects of extracellular anions, ruminal fermentation products, and transport inhibitors on the intracellular free Mg2+ concentration ([Mg2+]i), Mg2+ uptake, and intracellular pH were determined. Under control conditions (HEPES-buffered high-NaCl medium), the [Mg2+]i of REC increased from 0.56 ± 0.14 to 0.76 ± 0.06 mM, corresponding to a Mg2+ uptake rate of 15 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…In our previous work, a Na ϩ -independent H ϩ extrusion and an inhibition of electrodiffusive Mg 2ϩ uptake by vH ϩ -ATPase inhibitors have been observed in REC (41). Since these preliminary data point to a possible role of vH ϩ -ATPases in REC pH i regulation and solute transport, functional and molecular experiments were performed in this study to find direct evidence for the existence of such transport proteins in these Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In our previous work, a Na ϩ -independent H ϩ extrusion and an inhibition of electrodiffusive Mg 2ϩ uptake by vH ϩ -ATPase inhibitors have been observed in REC (41). Since these preliminary data point to a possible role of vH ϩ -ATPases in REC pH i regulation and solute transport, functional and molecular experiments were performed in this study to find direct evidence for the existence of such transport proteins in these Fig.…”
Section: Discussionmentioning
confidence: 60%
“…For years, the transport of these substrates has been known to be energized by a Na ϩ -motive force generated by the Na ϩ ,K ϩ -ATPase, which is expressed at high levels (19,27) and accounts for ϳ22-25% of the rumen O 2 and, consequently, ATP utilization (26). Recently, we found indirect functional evidence that a second active transport mechanism, namely a vacuolar-type H ϩ -adenosine triphosphatase (vH ϩ -ATPase), is present in the cell membrane of sheep rumen epithelial cells (REC) (41). In this study, Mg 2ϩ influx and thereby the free intracellular Mg 2ϩ concentration was reduced after application of the specific vH ϩ -ATPase inhibitors bafilomycin A 1 and foliomycin.…”
mentioning
confidence: 99%
“…This variable interaction between K 1 intake and Mg 21 absorption has been quantified, permitting the prediction of Mg absorption (Weiss, 2004). The K 1 -insensitive Mg 21 absorption in the presence of high ruminal potassium is due to a second, electroneutral mechanism of Mg 21 absorption (Leonhard-Marek and Martens, 1996;Leonhard-Marek et al, 1998b Leonhard-Marek et al, 1998a, Leonhard-Marek, 1999Schweigel and Martens, 2003 (Schweigel and Martens, 2003;Etschmann et al, 2006).…”
Section: Absorption Of Magnesiummentioning
confidence: 99%
“…The stimulating effects of SCFA and amiloride (increased availability of protons because of blocked NHE) have therefore suggested that Ca 21 /H 1 antiporters contribute to apical Ca 21 uptake (Schrö der et al, 1997 and. However, in the light of the presence of a ruminal vH 1 -ATPase (Schweigel and Martens, 2003;Etschmann et al, 2006), these findings might be additionally explained as a stimulation of other Ca 21 transport proteins by an apical pH microclimate. An increased electrogenic Na 1 absorption in the absence of divalent cations as shown for rumen and omasum (see above), is a feature of many Ca 21 channels (Sather and McCleskey, 2003;Hoenderop et al, 2005 (Pietrobon et al, 1989;Vennekens et al, 2001), so that an increased uptake of Cl 2 or SCFA 2 in exchange for bicarbonate could stimulate a luminal Ca 21 conductance via an increase in surface pH.…”
Section: Absorption Of Calciummentioning
confidence: 99%
“…In fact, renal epithelial cells accumulate Mg 2+ as a result of phosphate (Dai et al, 1997) or potassium (Dai et al, 1991) redistribution across the cell membrane. The dependence of Mg 2+ accumulation on K + redistribution across the plasma membrane suggests that Mg 2+ transport is the result of changes in membrane potential, possibly for charge compensation (Schweigel et al, 1999;Tashiro et al, 2002;Schweigel and Martens, 2003). In this respect, it is interesting to note that pathological conditions characterized by a marked decrease in tissue Mg 2+ content (e.g., diabetes) (Fagan et al, 2004) are also characterized by an inability to properly transport potassium (Mondon et al, 1974;Taylor and Agius, 1988).…”
Section: Role Of Egfmentioning
confidence: 99%